2023
DOI: 10.3389/fcimb.2023.1128577
|View full text |Cite
|
Sign up to set email alerts
|

The buzz in the field: the interaction between viruses, mosquitoes, and metabolism

Abstract: Among many medically important pathogens, arboviruses like dengue, Zika and chikungunya cause severe health and economic burdens especially in developing countries. These viruses are primarily vectored by mosquitoes. Having surmounted geographical barriers and threat of control strategies, these vectors continue to conquer many areas of the globe exposing more than half of the world’s population to these viruses. Unfortunately, no medical interventions have been capable so far to produce successful vaccines or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 259 publications
0
3
0
Order By: Relevance
“…This is consistent with a previous study on dengue virus ( 30 ), which observed that a lower blood meal titer resulted in lower viral loads in mosquito tissues even during the crossing of subsequent infection barriers at later timepoints. Several host machinery including those of glucose metabolism, lipid/phospholipid metabolisms, cell proliferation, apoptosis, and immunity have been shown to influence virus infection in mosquitoes ( 31 36 ). It is possible that a higher amount of virus initiating the infection could manipulate these host machineries at a larger scale in mosquito tissues and thereby enhance virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous study on dengue virus ( 30 ), which observed that a lower blood meal titer resulted in lower viral loads in mosquito tissues even during the crossing of subsequent infection barriers at later timepoints. Several host machinery including those of glucose metabolism, lipid/phospholipid metabolisms, cell proliferation, apoptosis, and immunity have been shown to influence virus infection in mosquitoes ( 31 36 ). It is possible that a higher amount of virus initiating the infection could manipulate these host machineries at a larger scale in mosquito tissues and thereby enhance virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota composition varies depending on the sex of the mosquito, developmental stage, larvae diet, blood source, ecology, geographical location, temperature, mosquito genetics, and metabolism (Minard et al, 2018 ; Parry et al, 2018 ; Bogale et al, 2020 ; Onyango et al, 2020 ; MacLeod et al, 2021 ; Pérez-Ramos et al, 2022 ; Sarma et al, 2022 ; Ratnayake et al, 2023 ; Rodpai et al, 2023 ). Water microbiota composition is also influenced by larval feces and the egestion of microorganisms by females during oviposition (Guégan et al, 2018 ; Scolari et al, 2019 , 2021 ).…”
Section: Mosquitoes and Arbovirusmentioning
confidence: 99%
“…Each of these complications reflects the intricate relationship between the virus and the CNS, emphasising the need for a comprehensive understanding of the diverse neurological sequelae that can arise. In navigating the clinical landscape of neurological manifestations, it becomes evident that vector‐borne viruses, with their diverse tropisms and complex interactions, have the potential to unravel a multitude of neurological complications 62,63 . From the acute to the chronic, from the central to the peripheral, each manifestation offers a unique glimpse into the intricate dance between these viral invaders and the intricate anatomy of the nervous system 64 …”
Section: Clinical Spectrum Of Neurological Manifestationsmentioning
confidence: 99%